The neurodevelopmental outcomes of perinatally HIV-infected children on different antiretroviral treatment (ART) strategies - Laughton, Barbara (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2019.